2017
DOI: 10.1001/jamaneurol.2017.0244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amyloid Protective Factors and Alzheimer Disease Neurodegeneration Protective Factors in Elderly Individuals

Abstract: IMPORTANCE While amyloid and neurodegeneration are viewed together as Alzheimer disease pathophysiology (ADP), the factors that influence amyloid and AD-pattern neurodegeneration may be considerably different. Protection from these ADP factors may be important for aging without significant ADP. OBJECTIVE To identify the combined and independent protective factors for amyloid and AD-pattern neurodegeneration in a population-based sample and to test the hypothesis that "exceptional agers" with advanced ages do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
93
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 72 publications
11
93
3
1
Order By: Relevance
“…From the sensitivity SEM analyses in Figure 4, we found that the primary predictor of the association between vascular health and ERC-tau seen in Figure 2 was hyperlipidemia. In our recent study 34 as well as this paper, we found evidence that lipids play an important role in the pathogenesis of processes upstream to AD neurodegeneration. Using Tau-PET and amyloid PET together here, we were able to further discern that tau deposition is specifically influenced by hyperlipidemia.…”
Section: Discussionsupporting
confidence: 65%
“…From the sensitivity SEM analyses in Figure 4, we found that the primary predictor of the association between vascular health and ERC-tau seen in Figure 2 was hyperlipidemia. In our recent study 34 as well as this paper, we found evidence that lipids play an important role in the pathogenesis of processes upstream to AD neurodegeneration. Using Tau-PET and amyloid PET together here, we were able to further discern that tau deposition is specifically influenced by hyperlipidemia.…”
Section: Discussionsupporting
confidence: 65%
“…Long‐term exposure to vascular risk factors through adulthood, including diabetes mellitus, hypertension, hypercholesterolemia, and obesity, are likely to impair brain health by altering the structure and function of cerebral blood vessels, limiting blood flow, and therefore reducing the availability of oxygen and glucose to the brain. Additionally, the relationship between vascular risk factors and neurodegenerative processes has been suggested in recent epidemiological studies that show an association between vascular risk factors and markers of neurodegeneration 27. All together, these data suggest that modifiable vascular risk factors may impact neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 69%
“…[12][13][14] However, the evidence is mixed as to whether a relationship exists between vascular risk factors and Aβ burden measured concurrently in older adults, 10,12,15 with recent data from our group suggesting no relationship. [12][13][14] However, the evidence is mixed as to whether a relationship exists between vascular risk factors and Aβ burden measured concurrently in older adults, 10,12,15 with recent data from our group suggesting no relationship.…”
mentioning
confidence: 81%